EXAMINING THE LEADERSHIP AND PERFORMANCE RELATIONSHIP IN HIGHER EDUCATION: SEQUENTIAL MEDIATION OF QUALITY ASSURANCE AND ORGANIZATIONAL COMMITMENT - Erni Murniarti; Julinda Siregar; Masda Surti Simatupang; Ramot Peter; Goklas Siahaan; Al Ghazali Al Ghazali (Nurul Jadid University, 2026)
This study examines the intricate relationship between transformational leadership (TL) and organizational performance (OP) within the higher education sector in Indonesia, emphasizing the sequential mediating roles of quality assurance (QA) practices and organizational commitment (OC). Drawing on the Resource-Based View (RBV) and Social Exchange Theory (SET), this research proposes that transformational leadership fosters robust quality assurance systems, which in turn enhance employees' affective commitment, ultimately improving institutional performance. Data were collected via structured questionnaires from 427 academic and administrative staff in accredited public and private universities in Indonesia, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that transformational leadership does not directly influence organizational performance (β = 0.082, p = 0.225), but exerts a strong positive effect on quality assurance (β = 0.672, p < 0.001), which in turn significantly enhances organizational commitment (β = 0.658, p < 0.001) and ultimately drives organizational performance (β = 0.551, p < 0.001). Most importantly, the full sequential mediation pathway TL → QA → OC → OP was confirmed significant (β = 0.244, p < 0.001; CI [0.171, 0.261]), demonstrating that transformational leadership improves institutional performance exclusively through the institutionalization of quality assurance and the cultivation of staff commitment. These findings contribute to theory by integrating RBV and SET into a unified sequential mediation framework, and offer practical guidance for university leaders and policymakers seeking to strengthen internal quality culture and human capital development in Indonesian higher education.